Diabetes knowledge and self-efficacy among rural women in Gujarat, India. - Mehta, Naaman V; Trivedi, Mayur; Maldonado, Luis E; Saxena, Deepak; Humphries, Debbie L (Rural and remote health, 2016)
Type II diabetes has risen dramatically among rural women in India, specifically in the states of Gujarat, Karnataka, Tamil Nadu and Uttar Pradesh. Recent studies suggest that rural Indian women's low level of self-efficacy, or confidence in their ability to carry out tasks, such as managing diabetes, is a key reason for this increase. Therefore, this study utilizes the Health Belief Model to analyze whether increased awareness of diabetes leads to a positive increase in levels of self-efficacy among diabetic women in two rural villages of Gujarat.